Estimating long-run equilibrium relationship between government expenditures and revenues in Romania - Nalban Valeriu (Budgetary Research Review (BRR), 2010)
This study examines the long-run relationship between government expenditures and revenues series for Romania. The available quarterly data for these variables covers 1995 - 2007 period. Due to the large economic turbulences in 2008 and 2009 the database will not consider these years. After running the Granger causality test, two cointegration approaches are used to prove the existence of a long-run fiscal equilibrium. Engle and Granger, respectively Johansen methodologies accept the existence of at least one significant cointegration relation. The results confirmed the hypothesis of no secular tendencies of budgetary imbalances.
Keywords: H6; 330